PENGARUH MASSASE PUNGGUNG DAN ALIH BARING TERHADAP KEJADIAN DEKUBITUS DI RUANG ICU RUMAH SAKIT GRAHA KEDOYA JAKARTA BARAT - Sumerti Lubis; Dewa Ayu Sri Saraswati (STIKes IMC Bintaro, 2018)
Introduction. Decubitus wound is a cellular necrosis that tends to result from prolonged compression of the soft tissues between bony bulge and a dense surface, most commonly caused by immobilization. Research Porpuse this study was to determine the effect of back mass and lethal exercise on prevention of decubitus occurrence in ICU patients at West Jakarta Grha Kedoya Hospital. Research methodology.This study research Quasi Experimental research design with pre-test approach and post-test non equivalent control group design. The population in this study were patients who had bed rest in hospital ICU with decubitus according to criteria. Samples studied in this study were 22 controls and 22 intervention groups. The result of the research .Then there is the influence of back massages and overlapping of the incidence of decubitus in the ICU Graha Kedoya Hospital, West Jakarta. This means that thre are Data obtained and analyzed by t-test. Based on t test result obtained in this research is p value 0,031. Conclusion then there is the influence of back massages and overlapping of the incidence of decubitus in the ICU Graha Kedoya Hospital, West Jakarta. Suggestion it is expected that there will be increased action in prevention of decubitus especially in ICU room.